Left internal jugular vein approach to right atrial appendage base implantation of the Aveir AR leadless pacemaker - Howard Liu; Daniel Cortez (Indian Pacing and Electrophysiology Journal)
Introduction: There is no prior report of an Aveir leadless pacemaker implantation into the atrial appendage via the internal jugular vein. Case: A 44-year-old female patient with history of multiple ablations for sinus node dysfunction presented with symptomatic bradycardia. The patient had femoral veins <9mm, chronic pain at the femoral vein insertion sites, as well as a recent car accident with persistent leg pain due to femoral fractures. Placement of a leadless pacemaker was decided based on patient discretion. An Abbott Aveir AR leadless pacemaker was implanted via left internal jugular vein access without complication. Post device implantation showed threshold of 0.75V @0.4 ms, impedance of 340 Ω, Pwave of 4.4 mV. Six-month follow-up demonstrated a threshold of 0.5 V @0.2 milliseconds, impedance of 300 Ω and Pwave of 7.2 mV with 92 % pacing and predicted longevity of 12.7 years. Discussion: The follow-up showed no complications in the patient. A similar approach may be feasible for other patients needing atrial leadless pacing, in which the transfemoral approach is not preferred. Conclusion: Implantation of the Aveir AR leadless pacemaker into the right atrial appendage is feasible via the left internal jugular vein.